Geological characterization of the tourist attractions of Itambé do Mato Dentro (MG) as a subsidy for the planning of ecotourism (Research, Society and Development, 2018)
Tourism comprises an important economic activity that aims to promote a region development by exploring its most relevant aspects, such as natural resources, cultural and historical characteristics, as well as geological elements, among others. In this context, the objective of this research was to characterize the tourism resources of the municipality of Itambé do Mato Dentro (MG) under a geological perspective and to evaluate its tourism potential. For data collection, documentary analysis and the observation of eight tourist attractions located in the city were used. Considering the infrastructure for the development of tourism in the region, it was found that the trails of access to tourist attractions have a degree of difficulty ranging from easy to moderate, yet not all places have enough signage. From the geological perspective it was observed that in the region quartzite rocks appear correlated to the Itambé do Mato Dentro Unit, Sopa-Brumadinho Formation, belonging to the Espinhaço Supergroup. In general, there is a need to plan tourism activities in the region, as well as the development of environmental education programs, involving residents and tourists, about the importance of environmental preservation.